2017
DOI: 10.1080/14649365.2017.1301541
|View full text |Cite
|
Sign up to set email alerts
|

Path-dependency in segregation and social networks in the Netherlands

Abstract: Policy-makers in industrialised countries have been implementing polices to create neighbourhoods with diverse populations in the hopes of increasing and ameliorating inter-ethnic relations. However, social networks seem to remain largely segregated. The composition of people's social networks is traditionally explained by population compositions and subsequent meeting opportunities versus preferences for homophilious interaction. Little attention has been paid to the social construction behind these two facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 72 publications
0
8
0
1
Order By: Relevance
“…It states that 'housing history matters' in terms of the existing built-up environment and the neighbourhood as well as with regards to institutional arrangements and policy (De Decker et al, 2011). 'Path-dependency' also exists, as Heringa et al (2018) describe, because future behaviour, in this case in relation to both residential choices and increased opportunities in obtaining primary (regular) housing, is embedded in past actions and current situations whilst also depending on the 'knowledgeability' (language, spatial environment, social systems) of individuals and the information and values that they have obtained through interactions with others. Institutional arrangements in terms of, for example, organising reception, and the implementation of policy by means of whether or not to activate or mobilise asylum seekers, have a direct effect on how such interactions take place and what social possibilities are available to asylum seekers.…”
Section: From An Asylum To a Housing Crisis For Refugeesmentioning
confidence: 99%
See 2 more Smart Citations
“…It states that 'housing history matters' in terms of the existing built-up environment and the neighbourhood as well as with regards to institutional arrangements and policy (De Decker et al, 2011). 'Path-dependency' also exists, as Heringa et al (2018) describe, because future behaviour, in this case in relation to both residential choices and increased opportunities in obtaining primary (regular) housing, is embedded in past actions and current situations whilst also depending on the 'knowledgeability' (language, spatial environment, social systems) of individuals and the information and values that they have obtained through interactions with others. Institutional arrangements in terms of, for example, organising reception, and the implementation of policy by means of whether or not to activate or mobilise asylum seekers, have a direct effect on how such interactions take place and what social possibilities are available to asylum seekers.…”
Section: From An Asylum To a Housing Crisis For Refugeesmentioning
confidence: 99%
“…Life paths, daily or long-term, are defined by socialisations which take place in specific spatial environments. These socialisations influence subsequent choices and possibilities in residential location, activity patterns and social networks (Heringa et al, 2018). Despite acknowledgement that domopolitics has an impact on the daily lives of asylum seekers, there is a total absence in asylum policy of vision concerning asylum seekers as 'residents' and reception contexts as 'living environments'.…”
Section: The Interrelation Between Spatial Contexts Social Network and Domopolitics Defining Path Dependencymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the alleged existence of such evidence, the link between social mix and social relations has been challenged (Wessel, 2009;Selim, 2015;Tersteeg & Pinkster, 2015). In this regard, it has been noted that the residential proximity between households or groups belonging to different social classes can favour contact, but this does not necessarily reverberate in subsequent social cooperation and a positive flow of capital from the middle class to the lower class (Heringa et al, 2017). It has been observed that in urban areas with some social mix, for example, where urban renewal processes have attracted a middle class (Malheiros et al, 2013), or in areas where processes of urban decay have attracted families with fewer resources (Alves, 2017a), the symbolic and/or cultural distance associated with linguistic differences and lifestyles tends to be more important than the fact that people live nearby.…”
Section: On the Effects Of Social MIXmentioning
confidence: 99%
“…Bolt (2009), who finds that social mix policies fall short of expectations, claims that such policies are based on several erroneous assumptions, such as the significance of neighbourhood as a space in which social practices play out, and the preferences of communities in terms of socializing. Heringa et al (2017) also claim that certain categories do not really focus upon their neighbourhood for the purposes of social activity and interaction, but prefer socializing with people who are similar in terms of age, social and ethnic background, social status and ambition, feeling alienated and out of place when they are surrounded by people who are 'different'. This claim is not confirmed by other empirical studies.…”
Section: Concerns and Assumptions Underlying Ideas Of Social MIX And mentioning
confidence: 99%